Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 51436 by Tawa1 last updated on 26/Dec/18

If    y = (((e^x  + e^(−x) ). tanh x)/(e^x  − sinh x))  prove that       y′  =  2 sech^2  x

Ify=(ex+ex).tanhxexsinhxprovethaty=2sech2x

Answered by peter frank last updated on 26/Dec/18

y(e^x −sinh x)=(e^x +e^(−x) )tanh x  recall  sinh x=((e^x −e^(−x) )/2)  tanh x=((e^x −e^(−x) )/(e^x +e^(−x) ))  substitute and simplify  y=((e^x −e^(−x) )/(e^x +e^(−x) ))  y^′ =((2.2)/((e^x +e^(−x) )^2 ))   y^′ =(4/((e^x +e^(−x) )^2 ))=sech^2 x  y^′ =sech^2 x  plz check

y(exsinhx)=(ex+ex)tanhxrecallsinhx=exex2tanhx=exexex+exsubstituteandsimplifyy=exexex+exy=2.2(ex+ex)2y=4(ex+ex)2=sech2xy=sech2xplzcheck

Commented by Tawa1 last updated on 27/Dec/18

God bless you sir

Godblessyousir

Terms of Service

Privacy Policy

Contact: info@tinkutara.com